Viabilidade do uso de bactérias lácticas em marcas comercializadas de leite fermentado - Rossetto, Bruna Thais (2015)
Currently this growing phase in the search for a healthy and nutritionally correct life, and foods that meet those specifications have been increasingly accepted by the population. Because of this industry conduct research aimed at the use of microorganisms that contribute to this healthy lifestyle, a great example of functional food are fermented milk plus lactic acid bacteria which is to regulate the digestive system function such as increased immunity human organism. The present study was to evaluate the viability of these bacteria as well as the physicochemical and microbiological characteristics of three brands marketed fermented milk checking whether they were within the parameters required by Brazilian law. The values found in all analyzes meet the parameters required by the country, and the lactic acid bacterial count exceeded the amounts required in this way guaranteed that all products evaluated in this study contribute positively to health of the population that consumes them.